Prospects of Veneering and Plywood Industries in Madhya Pradesh - Seth, V. K. (Indian Forester, 1974)
Inspite of its rich forest resources and its central location, the State of Madhya Pradesh does not have a single veneering and plywood unit. In this paper an appraisal has been made of the forest potential of the State, and a plea has been made for the esablishment of six units, which would require 20,000 cubic metres of Teak timber and 70, 000 cubic metres of miscellaneous timber. Likely locations of the proposed six units have been indicated. These units could produce 11.25 million sq. metres of plywood. Investments on setting up the units would be Rs.90 million. Market value of manufactured items would be Rs. 105 million. Royalty earning of Forest Department would be Rs.27 million annually. Employment generation potential would be 10,000.